2020
DOI: 10.5755/j01.itc.49.4.27386
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Missing Data Imputation in Big Data Interface

Abstract: The three-stage approach for missing data imputation in Big data interface is proposed in the paper. The first stage includes designing the Big data model in the task of missing data recovery, which enables to process the structured and semistructured data. The next stage is developing the method of missing data recovery based on functional dependencies and association rules. The estimating the algorithm complexity for missing data recovery is provided at the last stage. The proposed method of missing data rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In this manner, to bring down the issue of lost values in other attributes, the "Mean substitution-based imputation" approach has been utilized to substitute the lost entries with measurable approximations of the adjacent entries. The selected substitution approach i.e., "mean substitution-based imputation" [27] figure out the average estimate of the features and custom this average estimate to supply the lost entry.…”
Section: Filter For Substituting Lost Valuesmentioning
confidence: 99%
“…In this manner, to bring down the issue of lost values in other attributes, the "Mean substitution-based imputation" approach has been utilized to substitute the lost entries with measurable approximations of the adjacent entries. The selected substitution approach i.e., "mean substitution-based imputation" [27] figure out the average estimate of the features and custom this average estimate to supply the lost entry.…”
Section: Filter For Substituting Lost Valuesmentioning
confidence: 99%
“…Therefore, they showed that missing data imputation helps improve the application's result. Wang et al [34] proposed a missing data imputation method based on functional dependencies and association rules. The authors first modeled a big data schema in which the record's attributes describe a specific object.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the time analysis, their approach has better results than SVM, EM, and association rules. The main difference between [34] and our work is that they did not address an online scenario, thus using all the data available in the dataset.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to many forms of incompleteness and uncertainty, which is typical of many application tasks. In terms of the missing data issue, there are many effective methods of regression modeling based on machine learning for data imputation [22]. As far as large amounts of data are concerned, the development of a modern neural network toolkit for data flow processing allows of fulfilling these tasks with high accuracy [5,6].…”
Section: Introductionmentioning
confidence: 99%